Pelatihan dan Penguatan Literasi Digital Bagi Taman Baca Masyarakat (TBM) Galeri Kreatif Sebagai Komunitas Binaan Rumah Baca AQIL Kota Malang Jawa Timur - Wulandari, Istiqomah; Purwaningtyas, Isti; Hapsari, Dyah Eko; Fatimah, Fatimah; Az-Zahrah, Wardah; Alifah, Nurul; Sianipar, Grace Agatha; Al Fatah, M. Yanuar Al Fatah (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
In this era of rapid technological advancement, society needs to be equipped with the skills to discern reliable information. Digital literacy is an important foundation for society to be able to use information technology appropriately, ethically, and responsibly. This serves as the foundation for the Community Service Team from the English Literature Program at the Faculty of Letters, University of Brawijaya, to initiate a training and digital literacy enhancement program for the community, specifically targeting the Aqil Reading House community, particularly the Kampung Cerdas Ceria Creative Gallery Foundation, also known as TBM Creative Gallery, as one of the program's partners. This activity aims to empower the community by strengthening their understanding of digital concepts and skills. Specifically, the activity seeks to conduct training on four digital competencies: digital skills, digital ethics, digital safety, and digital culture, as well as provide guidance to the community in optimizing the use of widely available digital learning resources and information. This activity is expected to broaden knowledge about the concept of digital literacy and its implementation so that universities can formulate policies that will support efforts to empower communities with broad digital literacy. Institutionally, this activity is a manifestation of FIB UB's role in building a society that is able to utilize digital resources to the fullest and responsibly.